Pelatihan Instalasi Listrik yang Standar Sebagai Upaya Mendukung Peralihan Dari Kompor Gas LPG ke Kompor Listrik Di Desa Sandik, Kecamatan Batulayar - Sultan; Nrartha, I Made Ari; Muljono, Agung Budi; Sasongko, Sudi Maryanto Al; Ginarsa, I Made; Harjian, Muhammad Rivaldi; Widianty, Desi (Universitas Mataram, 2025)
This community service program aims to empower residents of Sandik Village, Batulayar District, West Lombok, in preparation for the transition from using LPG gas stoves to electric stoves. Given the urgent need to switch to more environmentally friendly energy, this activity focuses on electrical installation training that meets safety and efficiency standards. This training is designed to provide an in-depth understanding of installation procedures, handling of electrical equipment, and safety in using electric stoves. The training activities involve the participation of experienced electricians and practitioners, who provide comprehensive materials and demonstrations. Participants are trained in correct electrical installation techniques, and are taught about the importance of regular maintenance and inspections to prevent potential hazards. In addition, this program also includes giving prizes to outstanding participants and handing over donations of electric stoves to the village office as a symbol of support and commitment to the energy transition. The results of this program are expected to include increasing community knowledge and skills in carrying out electrical installations, as obtained from the results of the participant knowledge test which averaged above 70, or 68%, in addition to the readiness of household infrastructure for the use of electric stoves, and strengthening awareness of the importance of clean energy. The success of this program will be measured based on an assessment of the improvement in participants' skills, readiness of installation in residents' homes, and the ability of the community to adopt new technologies effectively and sustainably. Keywords: Installation, Electrical, Stove, Induction